Invasive Aquatic Animal Species in Indonesia: A Review - Hutabarat, Philipus; Salsabila, Salma; Putri, Valentina Yasmin Nursyah; Bagaskara, Ragil Damar; Putri, Noviana Pratama; Khoirinisa, Fitri; Margaretha, Argya; Vauzcika, Aura Nur; Ero, Sisilia Theresia Yuliani; Wiranti, Dinda Devina Putri; Syabani, Fahmi Rahman; Rahayu, Siti Mira; Sanjayasari, Dyahruri (MAIYAH, 2024)
This study examines the impact of invasive fish species in Indonesia, which is an important issue in efforts to maintain the sustainability of aquatic ecosystems. This study aims to identify existing non native fish species and evaluate their impact on local biodiversity. The methods used included a literature review and field surveys to collect data on the distribution of invasive species. The results showed that invasive species not only threaten the existence of native species, but also disrupt the overall balance of the ecosystem. The findings highlight the importance of effective management to prevent the further spread of invasive species, as well as the need for increased public awareness of their negative impacts. This research is expected to contribute to the development of better aquatic resource management strategies.